Analysis of epigenetic factors in mouse embryonic neural stem cells exposed to hyperglycemia - Shyamasundar, Sukanya (2014)
Background: Maternal diabetes alters gene expression leading to neural tube defects (NTDs) in the developing brain. The mechanistic pathways that deregulate the gene expression remain unknown. It is hypothesized that exposure of neural stem cells (NSCs) to high glucose/hyperglycemia results in activation of epigenetic mechanisms which alter gene expression and cell fate during brain development. Methods and Findings: NSCs were isolated from normal pregnancy and streptozotocin induced-diabetic pregnancy and cultured in physiological glucose. In order to examine hyperglycemia induced epigenetic changes in NSCs, chromatin reorganization, global histone status at lysine 9 residue of histone H3 (acetylation and trimethylation) and global DNA methylation were examined and found to be altered by hyperglycemia. In NSCs, hyperglycemia increased the expression of Dcx (Doublecortin) and Pafah1b1 (Platelet activating factor acetyl hydrolase, isoform 1b, subunit 1) proteins concomitant with decreased expression of four microRNAs (mmu-miR-200a, mmu-miR-200b, mmu-miR-466a-3p and mmu-miR-466 d-3p) predicted to target these genes. Knockdown of specific microRNAs in NSCs resulted in increased expression of Dcx and Pafah1b1 proteins confirming target prediction and altered NSC fate by increasing the expression of neuronal and glial lineage markers. Conclusion/ nterpretation: This study revealed that hyperglycemia alters the epigenetic mechanisms in NSCs, resulting in altered expression of some development control genes which may form the basis for the NTDs. Since epigenetic changes are reversible, they may be valuable therapeutic targets in order to improve fetal outcomes in diabetic pregnancy.